Central bank transparency and green innovation policy in Indonesia - Alim, Muhammad Birrul; Setiyantono, Aulia Pamasa; Maqfiroh, Selvi (Jurnal Ekonomi Indonesia, 2025)
A green economy is a sustainable and environmentally friendly development model. The green economy is expected to improve people's welfare without compromising the quality of the environment and natural resources. The purpose of this study is to determine the long-term and short-term relationship between monetary variables, namely interest rates, broad money, and central bank transparency, on the green economy in Indonesia. This study uses ARDL analysis with a sample period of 1999Q1 to 2019Q4. The results of short-term ARDL research show that green innovation is significantly influenced by innovation in the previous period, interest rates, and central bank transparency. Green innovation tends to increase when influenced by past performance and accommodative monetary policy, although some factors show the opposite impact in specific periods. Meanwhile, the effect of money supply on green innovation is dynamic, initially showing a significant positive impact in the short term but becoming negative in the subsequent period. Central bank transparency is also significant, with a positive direction in lag one and a negative in lag 2.